Gross Anatomical Studies on the Embryonic Heart Development in Goat (Capra hircus) - Gupta, S. K.; Pathak, Archana; Farooqui, M. M.; Prakash, Ajay (Indian Journal of Veterinary Anatomy, 2017)
The topographical and morphological study of the goat embryo showed that initially on 23rd day of gestation, the primitive tubular heart was situated in the region of cervical flexure and its distal extremity was beyond the lower end of liver and no lungs were present in relation to heart. With the advancement of embryonic age much development in the morphology of the heart and change in the topographical predisposition takes place and finally it is converted into four chambered heart with both the longitudinal and transverse grooves. On 42nd embryonic day, the heart was caudodorsallyattached with the lungs and was situated in thoracic cavity, but separated from the liver by the septum transversarium (future diaphragm).